(untitled) (Altre Modernità, 2010)
Barack Obama’s election brought to the forefront one of the key figures of the nineteenth century, Abraham Lincoln, considered to be a founder of the nation by the new American President. Like Lincoln, Obama put the accent on unity and national goodwill. Like Lincoln, Obama nourished the roots that connected to the common man. The deep desire for change in American politics that Obama espouses also occurred during Lincoln’s presidency. This essay dwells on Lincoln’s words that are impressive in many respects, especially in the way they are able to communicate the passion of political involvement, as well as are impressive the images which represent the Great Emancipator in the different period of American history. Words and images reinterpreted Lincoln’s myth in a contemporary mood, showing the how Lincoln became a continuously changing icon, down to the current presidency of Barack Obama.